SPORT-SPHERE: A Review of AI-Driven Personalized Sports Updates for Multi-Discipline Enthusiasts - Chaudhari, Reddy; Pathak, Basha (Journal of Research in Science and Engineering, 2026)
This paper proposes SPORT-SPHERE, a novel AI-powered startup idea that transforms the sports update experience for cricket, F1, Golf, Tennis, and football enthusiasts. Leveraging machine learning, natural language processing, and data analytics, SPORT-SPHERE provides personalized, real-time, in-depth sports updates, news, and analysis. By addressing the limitations of existing sports update platforms, SPORT-SPHERE offers an exceptional user experience, increased engagement, and enhanced decision-making capabilities. This innovative platform is poised to disrupt the sports update industry and become a leading destination for sports enthusiasts worldwide. The sports industry has witnessed a significant surge in demand for real-time updates, in-depth analysis, and personalized content. This paper proposes a novel AI-powered startup idea, SPORT-SPHERE, which aims to revolutionize how cricket, Tennis, and football enthusiasts consume sports updates. By leveraging machine learning algorithms, natural language processing, and data analyt- ics, SPORT-SPHERE provides users with exceptional, personalized, real-time sports updates, news, and analysis.